ANALISIS PENINGKATAN DISIPLIN ANAK USIA DINI MELALUI PENERAPAN REWARD DI TKQ NURUL SHOBAH - Nurjaman, Iman; Nurlela, Sri; Handayani, Handayani; Riskiyani, Riska (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Early Childhood Education (ECE) plays a crucial role in character development, including discipline. This research aims to explore how the application of rewards can improve discipline in children aged 5-6 years at TKQ Nurul Shobah , Tangerang. The research employs a qualitative approach with a case study design. Data collection was conducted through (1) direct observation of children's behavior during daily routine learning activities, (2) interviews with classroom teachers and the school principal to gain insights into reward strategies and their impact on children's character, and (3) documentation for supporting evidence. Data analysis was performed descriptively and qualitatively through steps including data reduction, data presentation, and conclusion formation. The provision of rewards in shaping disciplined character in early childhood, particularly for Group B, involved various strategies, including the use of rewards. Teachers awarded stars to children who arrived early and provided praise to those who listened to instructions. The results indicate that the consistent use of verbal rewards (praise) and non-verbal rewards (stickers, smiles) positively affects children's disciplined behavior, such as arriving on time, following instructions, and tidying up toys. The use of praise as a reward motivates children, making them enthusiastic and feel valued.